(Un)separated by a common language?: Are American/British differences unimportant?. Issue 1 (3rd February 2016) - Murphy, M. Lynne
Abstract : Interest in the differences between English in Britain (or more especially England) and the United States supports a small industry, of which I am a small part. But there are those who argue that the differences are so negligible that they are not worth investigating. One of these is University of Edinburgh Professor of General Linguistics Geoffrey Pullum, who wrote a post on the topic for the Lingua Franca blog of the Chronicle of Higher Education . Pullum (2014) concluded:Looked at seriously, the tiny differences between standard American and standard British English are trivial, barely even worth mentioning. Pullum was motivated to make this argument for good reasons. He was fighting the exaggeration of the differences and pointing out that Britons and Americans generally understand each other well in spite of whatever differences there are. But at the same time, Pullum's argument rests on oversimplifications, just like the claims that he hopes to counter.